تأسيس بلدة سيدي عون ونشأتها خلال القرن 18 م. على ضوء المصادر المحلية والرواية الشفوية - صغيري، سفيان; قسيبه، رشيد (جامعة الشهيد حمّه لخضر الوادي - كلية العلوم الاجتماعية والإنسانية, 2022)
تعتبر بلدة سيدي عون من أقدم الحواضر والتجمعات السكانية التي نشأت في الجهة الشمالية من واد سوف، ونستهدف من خلال دراستنا توضيح أصولها بالعودة إلى مسيرة الجد سيدي عون الأكبر الذي يشكل أولاده وأحفاده النسيج الاجتماعي لسكان البلدة، خاصة الحفيد المؤسس سيدي عون الأصغر الذي تنسب إليه القرية، إضافة إلى الوافدين الذين امتزجوا مع سكان البلدة بالمصاهرة والنسب والإقامة الدائمة، معتمدين على ما دون من أثر وما تواتر من رواية شفوية التي تعتبر من أهم مصادر تاريخنا المحلي رغم ما تطرحه من ضرورة التحقيق والتدقيق. Sidi Aoun is one of the oldest cities and population centers that originated in the northern side of Oued Souf, And we aim, through our study, to clarify its origins by back to the autobiography of Grandfather Sidi Aoun alakbar whose children and grandchildren form the social fabric of the town’s residents, Especially the founding grandson of Sidi Aoun, the youngest to whom the village is attributed, In addition to the expatriates and the Barani who mixed with the residents of the town through intermarriage, lineage and permanent residence, Relying on the substantive and frequent oral narrative, which is considered one of the most important sources of our local history, despite what it raises of the necessity of investigation and scrutiny
Keywords: التاريخ الاجتماعي -- الذاكرة الشعبية -- الروايات الشفوية -- القرن الثامن عشر -- الجزائر